2008
DOI: 10.1039/b808513g
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of a novel cyclic C35-terpene via the cyclisation of a Z-type C35-polyprenyl diphosphate obtained from a nonpathogenic Mycobacterium species

Abstract: Lipid components from 12 nonpathogenic Mycobacterium species were analysed. A novel cyclic C(35)-terpene, named heptaprenylcycline , was obtained from 3 species, while octahydroheptaprenol , which has 3 Z-double bonds, was obtained from 6 species. The amounts of and in the cultured cells increased after the 4- to 6-d stationary phase. The yield of was considerably greater at a higher temperature of 37 degrees C than at an optimal temperature of 28 degrees C, while that of remained unchanged at all temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 31 publications
0
40
1
Order By: Relevance
“…[1][2][3] We have reported that two cyclic C 35 terpenes 1 and 2 are produced only by M. vanbaalenii and M. chlorophenolicum, which degrade environmental pollutants such as polycyclic aromatic hydrocarbons and pentachlorophenol, respectively. [1,2] Our previous studies [1,2] on the biosyntheses of C 35 terpenes by Mycobacterium species have demonstrated the following points: 1) C 35 terpenes 1-4 were produced by the methylerythritol phosphate (MEP) pathway; 2) 1 was formed by a biocyclization reaction of the Z-type C 35 polyprenyl diphosphate 5; 3) the oxygenation reaction of 1 to form 2 was catalyzed by the action of P450 monooxygenase (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] We have reported that two cyclic C 35 terpenes 1 and 2 are produced only by M. vanbaalenii and M. chlorophenolicum, which degrade environmental pollutants such as polycyclic aromatic hydrocarbons and pentachlorophenol, respectively. [1,2] Our previous studies [1,2] on the biosyntheses of C 35 terpenes by Mycobacterium species have demonstrated the following points: 1) C 35 terpenes 1-4 were produced by the methylerythritol phosphate (MEP) pathway; 2) 1 was formed by a biocyclization reaction of the Z-type C 35 polyprenyl diphosphate 5; 3) the oxygenation reaction of 1 to form 2 was catalyzed by the action of P450 monooxygenase (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This result establishes the efficacy of unbiased lipidomic screens to identify previously unknown compounds. A C35 terpene cyclase activity is found in nonpathogenic mycobacteria (31,32), but Rv3377c orthologs are only known within M. tuberculosis complex. Higher-order terpene-nucleosides are rare in nature, and we have not identified a precedent for 1-linked prenyl adenosines.…”
Section: Discussionmentioning
confidence: 99%
“…4, 13-18) that differ from sesquarterpenes 2-8 in B. subtilis have been found in nonpathogenic Mycobacterium species (Table 1). [32][33][34][35] Our biosynthesis study using cell-free extracts of M. chlorophenolicum indicated that a cyclic sesquarter- pene (heptaprenylcycline, 13) is biosynthesized via cyclization of a linear C 35 isoprenoid (19) (Fig. 4).…”
Section: Unique Biosynthesis Of Sesquarterpenes (C 35 Terpenes) Imentioning
confidence: 99%
“…4). 32) Recently it was reported that sesquarterpenes 2-8 in B. subtilis are produced via cyclization of a linear Etype C 35 isoprenoid. [26][27][28][29] On the other hand, the cyclization of a Z-type linear isoprenoid, as observed in the formation of 13, has rarely been described.…”
Section: Unique Biosynthesis Of Sesquarterpenes (C 35 Terpenes) Imentioning
confidence: 99%
See 1 more Smart Citation